Effectiveness of high-frequency individual reminiscence interventions using life story books on persons with dementia. (May 2021) - Asano, Tomoaki; Wang, Chih-Wen; Tsugaruya, Megumi; Ishikawa, Takashi
Introduction: Reminiscence therapy, using life story books, is a non-pharmacological treatment and helps promote psychosocial benefits in people with dementia. This research thus aimed to determine the effects of life story books among participants with dementia of different severities. Method: The experimental group ( n  = 36) underwent three semi-structured interviews over 10 weeks. After a 2-week life story books-production interval, the experimental group received the intervention over 4 weeks, five times weekly. The following 12 weeks were the follow-up period. The control group ( n  = 30) underwent the first and last assessments, with a 6-month interval, while receiving their usual care services. Results: Participants' cognitive functioning was mostly maintained at follow-up in the experimental group, but significantly declined in the control group. The experimental group showed no significant change in cognition among participants with severe dementia during all periods, assessed using the behavioural and psychological symptoms of dementia, and the caregivers' burden decreased significantly from before to after the intervention. Conclusion: These results demonstrate that life story book interventions are an effective tool in improving the relationship between caregivers and people with dementia, and could help people with dementia maintain cognitive function, even those with severe dementia.